A study of fatty acid composition and tocopherol content of marine microalgae, nannochloropsis oculata and tetraselmis suecica, using solvent extraction and supercritical fluid extraction - Bong, Shu Chin.
Microalgae, which comprise of all the eukaryotic photosynthetic microorganisms, contain rich amount of high value compounds such as fatty acids especially polyunsaturated fatty acids (PUFAs) and vitamins, unleashing their potential as functional food ingredients. Therefore, this study was conducted to investigate and compare the fatty acids and tocopherols of lipid extracted from marine microalgae, Nannochloropsis oculata (NO) and Tetraselmis suecica (TS) using solvent extraction and the environmental friendly supercritical fluid extraction (SFE). Fatty acids and tocopherols were determined in the extracted lipid as functions of the temperature (40, 80°C) and pressure (3000, 5000, 7000, 9000psi) Dichloromethane-methanol and hexane were the chosen conventional solvent for fatty acids and tocopherols extraction respectively. The results obtained showed that there were differences in the fatty acid composition of various lipid extracts of NO and TS. Extracts of NO were high in myristic acid (C14:0) (17-35%), palmitic acid (C16:0) (14-47%) and palmitoleic acid (C16:1) (11-42%) whereas extracts of TS were high in C14:0 (21-34%) and C16:0 (29-49%). Eicosapentaenoic acid (EPA) was detectable only under certain SFE condition in NO but was not detected in TS. Tocopherol composition of NO and TS were also different where α-, β- and γ-tocopherol were detected in various SFE extracts of NO (except under 40°C/3000psi where γ-tocopherol was not detected) but only α- and β-tocopherol were detected in such of TS. Hexane extraction of both NO and TS resulted in the detected of only α-tocopherol. The highest α-tocopherol concentration was obtained at 40oC3000psi for NO (10.353 ± 0.253 mg/g extract) and 80°C/3000psi for TS (0.963±0.290 mg/g extract), with α-tocopherol content of NO significantly higher (p<0.05) than that extracted using hexane (10.353 ± 0.253 vs 4.722 ± 0.405 extract). In conclusion, the use of different extraction methods have resulted in different compositions and concentration of fatty acids and tocopherols in microalgae studied.